Classic Congenital Adrenal Hyperplasia due to 21-Hydroxylase-Deficiency: 13 Years of Neonatal Screening and Follow-up in Bavaria - Odenwald, B.; Dörr, H.-G.; Bonfig, W.; Schmidt, H.; Fingerhut, R.; Wildner, M.; Nennstiel-Ratzel, U. (Klinische Pädiatrie, 2015)
Background: 21-Hydroxylase deficient (21-OHD) classic congenital adrenal hyperplasia (CAH) is a potentially lethal inherited endocrine disorder. It is included in many neonatal screening programs to prevent morbidity and mortality from salt-wasting and to reduce long-term health problems. This paper presents a population-based evaluation of CAH screening quality and outcome in Bavaria between 1999 and 2011 including long-term follow-up of patients.Methods: Screening process quality, clinical complications during the neonatal period, treatment and development of patients up to the age of 4 years were analysed.Results: Among 1 420 102 screened infants, 114 cases of 21-OHD classic CAH were detected (prevalence 1:12 457). Mean age at start of treatment was 7 days. However, in 29 cases (25.4%), age at start of treatment was 12 days or more. The frequency of neonatal salt-wasting increased with age at start of treatment, but all neonatal salt-wasting episodes and crises were managed successfully. Up to the age of 4 years, developmental assessment of the CAH cohort yielded normal results.Discussion: Epidemiological and screening effectiveness results are in keeping with other publications. For the most part, screening process times were compliant with guidelines. The Bavarian CAH screening and tracking system proved successful, but there were process delays and complications which might have been avoidable. The outcome supports the benefits of CAH screening, but further research is necessary to increase CAH screening effectiveness and to evaluate long-term effects.
Keywords: classic congenital adrenal hyperplasia; CAH; 21-hydroxylase deficiency; neonatal screening; long-term follow-up